Student Creativity in Poster Making Using Project Based Learning - Putri, Ananda; Nurhafifah, Ifah; Purbasari, Nurindah; Wardani, Rizka Ardya; Wahdiati, Atiti; Juwita Sari, Indah (Universitas Tidar, 2024)
This research analyzes students' creativity in making posters using the Project-Based Learning (PjBL) Model. This research uses a case study method. A case study is an empirical investigation that investigates a phenomenon in the context of real life. There are four aspects of creativity. First, creativity is defined as a force within the individual. Second, creativity is managing information and using skills and imagination to do or create something. Third, creativity produces something new or a work of art. Fourth, creativity is a product that is produced, for example, ideas, written works, or products. In this case, creativity shows students' ability to develop ideas about HIV and AIDS in poster form and complete posters on time. Poster-making is an assignment that will foster student creativity. In making posters, students will determine essential things about the material included in the poster. Therefore, using the Project-Based Learning (PjBL) model in the assignment to make posters in class X Science at one of the senior high schools in Serang City can initiate student creativity.